An evaluation of the sustainability of tourism in Barangay Mines View, Baguio City - Adiao, April Camille P.; Nacilla, Nica Jenine O. (2013)
Barangay Mines View is a residential-commercial division in Baguio City that s known for being a tourist destination due to its mountainous and former gold mine scenery. This qualitative research explores the perception of the residents regarding the effects of tourism in their place using sustainable tourism indicators forwarded by Mowforth and Munt and sustainability principles forwarded by Tisdell and Wen. This research employs George Homan's Social Exchange Theory in order to make sense why the residents are taking different course of actions when they are presented with the certain situations regarding tourism. The residents are divided into two types which are the directly involved and indirectly involved residents in terms of their employment and connection with the tourism activities in their area. Based on the data that were gathered, the residents acknowledge that there are certain benefits that they are reaping in such activities especially in the economic aspects. However, they also experience the cost of it which are shown in the cultural, social, environmental, aid to conservation, local participation and education spheres. The researchers concluded that the tourism in Barangay Mines View is unsustainable since there is an evident degradation of environment, non-aggressive conservation efforts, diminishing income in tourism business as well as the disparity among the residents in terms of local participation --Author's abstract.
Thesis (B.A.) -- University of the Philippines Baguio, 2013.
Includes bibliographical references (leaves 100-102)
Keywords: Sustainable tourism -- Philippines -- Mines View(Baguio City); Tourist trade -- Philippines -- Mines View(Baguio City) -- Economic aspects; Tourist trade -- Philippines -- Mines View(Baguio City) -- Environmental aspects